Gamedec. UKW in IGDA Curriculum Framework - Mochocki, Michał (Replay. The Polish Journal of Game Studies, 2017)
Launched in October 2013, GAMEDEC: game studies & Design is a specialisation track within the 2nd Gen Humanities (aka Humanities 2.0) 3-year BA programme at Kazimierz Wielki University (UKW) in Bydgoszcz, Poland. The curriculum was created by UKW academic staff with game design experience, guided by the IGDA 2008 Framework and consulted with game dev professionals. It underwent slight modifications in 2014 and a significant transformation in 2015. This paper aims at a thorough analysis of the structure of the curriculum as seen through the lens of the IGDA Framework (2008), including the coverage of both Core Topics and Institutional Considerations. The analysis is conducted in the context of foreign (mostly U.S.- based) game degrees and supported with comments on its design, implementation and modifications.